2020
DOI: 10.1200/go.20.00014
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival After Head and Neck Squamous Cell Carcinoma in South America: The InterCHANGE Study

Abstract: PURPOSE Head and neck squamous cell carcinoma (HNSCC) incidence is high in South America, where recent data on survival are sparse. We investigated the main predictors of HNSCC survival in Brazil, Argentina, Uruguay, and Colombia. METHODS Sociodemographic and lifestyle information was obtained from standardized interviews, and clinicopathologic data were extracted from medical records and pathologic reports. The Kaplan-Meier method and Cox regression were used for statistical analyses. RESULTS Of 1,463 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 30 publications
6
47
1
6
Order By: Relevance
“…This disease may rapidly invade or metastasize, and severe tumours may then require complex surgery and/or radiotherapy (occasionally, chemotherapy) that results in long‐term orofacial deformity, oropharyngeal dryness, trismus, a risk of osteoradionecrosis and reduced quality of life. Advanced cases are also associated with a lower likelihood of survival 2,15,16 . In Brazil, oral cancer is the fifth most incident type in men, comprising 5% of all cancer cases estimated for 2020 17 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This disease may rapidly invade or metastasize, and severe tumours may then require complex surgery and/or radiotherapy (occasionally, chemotherapy) that results in long‐term orofacial deformity, oropharyngeal dryness, trismus, a risk of osteoradionecrosis and reduced quality of life. Advanced cases are also associated with a lower likelihood of survival 2,15,16 . In Brazil, oral cancer is the fifth most incident type in men, comprising 5% of all cancer cases estimated for 2020 17 .…”
Section: Figurementioning
confidence: 99%
“…Advanced cases are also associated with a lower likelihood of survival. 2,15,16 In Brazil, oral cancer is the fifth most incident type in men, comprising 5% of all cancer cases estimated for 2020. 17 Prior research reports have shown an important reduction in the number of soft oral tissue biopsies in Brazil due to the pandemic.…”
mentioning
confidence: 99%
“…There is still a great lack of data relative to its clinical outcome, especially in South America (10). Considering Brazil, the studies carried out generally represent data from the Southeast region, to the detriment of the other regions (11).…”
Section: Oral Squamous Cell Carcinomas (Oscc)mentioning
confidence: 99%
“…The 5-year survival rates of patients with OSCC vary worldwide, from 26% to 72,5% (5, 10, 14-18). In South America, 3-year OS rate for OSCC was 54.7%, however more than half of the participants of the study were treated at private hospitals (10). Among Brazilian studies, the 5-year OS may vary regionally from 24% to 51.7% (6, 7, 20-26), and it was 30% for patients with OSCC undergoing outpatient cancer treatment by Brazilian Unified National Health System (27).…”
Section: /10mentioning
confidence: 99%
“…Head and neck squamous cell carcinomas (HNSCCs) are clinically complex and molecularly heterogenous [1]. Despite intensive studies of HNSCC and the development of new therapeutic modalities, the five-year survival rate has remained at 50% for decades [2][3][4]. One hallmark of HNSCC is the presence of hypoxic areas within the tumor tissue.…”
Section: Introductionmentioning
confidence: 99%